Analyzing Factors Contributing to Gender Inequality in Indonesia using the Spatial Geographically Weighted Logistic Ordinal Regression Model - Hani Khaulasari; Yuniar Farida (LPPM Institut Teknologi Sepuluh Nopember, 2024)
Abstract—Gender inequality is a condition of discrimination caused by social systems and structures. The main objective of this research is to identify factors that influence gender inequality in each province in Indonesia and obtain classification accuracy values using Geographically Weighted Ordinal Logistic Regres- sion (GWOLR). The dataset used in this research consists of a response variable, namely the gender inequality index where theindex value is divided into ordinal categories (low, medium, and high) and four predictor variables from the dimensions of health,education, human empowerment, social-culture, and work. Theresults of this study show that the classification accuracy of theGWOLR model is 85%. The mapping of provinces in Indonesiabased on influential variables forms three groups. The first group(brown) is influenced by the percentage of women who givebirth with the assistance of health workers (X 1 ) and the femaleHuman Development Index (HDI) (X3 ). The second group (blue)is influenced by the ratio of women’s Pure Participation Rate(APM) (X 2 ) and the percentage of rape crimes against women(X 4 ). The third group (red) is influenced by the percentage ofwomen who give birth with the assistance of health workers (X1),the ratio of women’s Pure Participation Rate (APM) (X2 ), thepercentage of women’s Human Development Index (HDI) ratio(X 3 ), and the percentage of women’s rape crimes (X4 ).